Can We Validate the Results of Twin Studies? A Census-Based Study on the Heritability of Educational Achievement - Schwabe, Inga; Janss, Luc; van den Berg, Stéphanie M. (Frontiers in Genetics, 2017)
As for most phenotypes, the amount of variance in educational achievement explained by SNPs is lower than the amount of additive genetic variance estimated in twin studies. Twin-based estimates may however be biased because of self-selection and differences in cognitive ability between twins and the rest of the population. Here we compare twin registry based estimates with a census-based heritability estimate, sampling from the same Dutch birth cohort population and using the same standardized measure for educational achievement. Including important covariates (i.e., sex, migration status, school denomination, SES and group size), we analyzed 893,127 scores from primary school children from the years 2008-2014. For genetic inference, we used pedigree information to construct an additive genetic relationship matrix. Corrected for the covariates, this resulted in an estimate of 85%, which is even higher than based on twin studies using the same cohort and same measure. We therefore conclude that the genetic variance not tagged by SNPs is not an artefact of the twin method itself.